Parasitic infestations in hybrid surubim catfish fry (Pseudoplatystoma reticulatum x P. corruscans) - De Pádua, Santiago Benites [UNESP]; Ishikawa, Márcia Mayumi; Kasai, Rodrigo Yutaka Dichoff; Jerônimo, Gabriela Tomas; Carrijo-Mauad, Juliana Rosa (My University, 2012)
This study evaluated parasitic infestations in the hybrid surubim catfish (Pseudoplatystoma reticulatum ♀ x P. corruscans ♂) during the initial phase of rearing. 50 fish of lengths ranging from 5.7 to 20.3 cm and weights from 1.2 to 48.8 g were examined. Among the fish evaluated, only 15 (30%) were parasite-free, while at least one type of parasite was diagnosed in all of the other 35 (70%). Among these, the protozoan Ichthyophthirius multifiliis, Epistylis sp. and Trichodina sp. were observed. Occurrences of myxosporidians were seen, represented by Henneguya sp. and a metazoan belonging to the class Monogenoidea. The ciliated protozoa I. multifiliis, Epistylis sp. and Trichodina sp. were the main parasites infesting the gills and tegument of hybrid catfish fry. The peritrichid Epistylis sp. may be an emerging parasite in Brazil.
Parasitic infestations in hybrid surubim catfish fry (pseudoplatystoma reticulatum x P. corruscans)
Keywords: Ciliophora; Fry; Monogenoidea; Myxosporea